PFAS Degradation in Ultrapure and Groundwater Using Non-Thermal Plasma - Davide Palma; Dimitra Papagiannaki; Manuel Lai; Rita Binetti; Mohamad Sleiman; Marco Minella; Claire Richard (Molecules, 2021)
Perfluoroalkyl substances (PFAS) represent one of the most recalcitrant class of compounds of emerging concern and their removal from water is a challenging goal. In this study, we investigated the removal efficiency of three selected PFAS from water, namely, perfluorooctanoic acid (PFOA), perfluorohexanoic acid (PFHxA) and pefluorooctanesulfonic acid (PFOS) using a custom-built non-thermal plasma generator. A modified full factorial design (with 2 levels, 3 variables and the central point in which both quadratic terms and interactions between couple of variables were considered) was used to investigate the effect of plasma discharge frequency, distance between the electrodes and water conductivity on treatment efficiency. Then, the plasma treatment running on optimized conditions was used to degrade PFAS at ppb level both individually and in mixture, in ultrapure and groundwater matrices. PFOS 1 ppb exhibited the best degradation reaching complete removal after 30 min of treatment in both water matrices (first order rate constant 0.107 min−1 in ultrapure water and 0.0633 min−1 in groundwater), while the degradation rate of PFOA and PFHxA was slower of around 65% and 83%, respectively. During plasma treatment, the production of reactive species in the liquid phase (hydroxyl radical, hydrogen peroxide) and in the gas phase (ozone, NOx) was investigated. Particular attention was dedicated to the nitrogen balance in solution where, following to NOx hydrolysis, total nitrogen (TN) was accumulated at the rate of up to 40 mgN L−1 h−1.